The Influence Of Work Period, Allowances, And Supervision On The Quality Of Work Of Physical Education Teachers In Facing Curriculum Changes In Kajen, Pekalongan RegencyLUM CHANGES IN KAJEN, PEKALONGAN REGENCY - JATI SETYO UTAMI; Rahayu, Tandiyo; Rahardjo, Hermawan Pamot (Journal of Physical Education and Sports, 2024)
This thesis aims to research and investigate the influence of the length of service, allowances, and supervision on the quality of work of Physical Education (PE) teachers at Korwil Kajen, Pekalongan Regency in facing curriculum changes. This research focuses on three main variables: length of service, benefits, and supervision, as factors that can influence the quality of teacher work. The research was carried out using a mixed approach (mixed methods) which combines qualitative and quantitative data. This research involved 52 PE teachers in the Kajen area, Pekalongan Regency. Primary data was obtained through interviews and direct observation, as well as secondary data from related documents. The indicators taken are planning, processes, evaluation and related documents. The validity of the data was tested through triangulation. The data analysis process involves collecting, presenting, and drawing conclusions. The results of the analysis show the diversity of learning practices of PE teachers, which reflects a commitment to quality learning with document preparation and involvement in supervision. However, supervision still has weaknesses that need to be corrected to increase its effectiveness. The analysis of PE teachers also highlights variations in educational practice and self-development, providing an overview of the potential for improvement and strengthening supervision. Recommendations can focus on improving practice, strengthening supervision, and professional development to achieve higher educational standards and to improve the quality of work and challenges in implementing the Merdeka curriculum. Based on the research results, it can be concluded that the length of service, allowances and supervision of PE teachers have an influence on the quality of work in facing curriculum changes. By referring to the research results, it is recommended that the Education Office develop training programs, optimize the use of allowances, and improve the quality of supervision. School principals are advised to implement different management approaches, encourage collaboration between teachers, and facilitate self-development programs. Meanwhile, PE teachers are advised to participate in training, use allowances wisely, be involved in collaboration and joint discussions, and be active in supervision programs. It is hoped that the implementation of these suggestions can improve the quality of PE teachers' work.